TEACHER’S BELIEF ABOUT DIGITAL LITERACY BASED ON THEORY OF PLANNED BEHAVIOR - Hening Laksani (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
Digital literacy is a significant component of 21st-century learning the teachers need to possess. In the education context, however, the impact of the rapid development of digital technologies requires teachers as learning facilitators and motivators to employ digital literacy to prepare the students in digital environments. In spite of its importance, research observing teachers’ belief about digital literacy in English Language Teaching context is limited. Hence, this study aims to investigate teachers’ belief about the integration of digital literacy in English Language Teaching particularly through three aspects of teacher’s belief namely teacher’s behavioral belief, normative belief and control belief. Accordingly, a descriptive study on English in-service teachers is used in this research. In this matter, the participants were purposively selected based on the consideration that the participants could give sufficient information to answer the research questions. In order to examine the topic, five English in-service teachers considered as the participants were examined through interviews as the data collecting techniques. The findings indicated that the behavioral belief was related to the implementation of the concept of digital literacy in terms of developing students’ 21st-century skills, normative belief dealt with the expectation in social context both administrators and parents, while control belief was about the availability of particular digital technology to be implemented in the classroom. The findings of this study expected to provide an overview of the teacher’s belief which drives the integration of digital literacy in the classroom. This study provides an overview of teachers’ beliefs in integrating digital literacy which help teachers to personalize their professional development to adjust the digital era into teaching-learning instructions.